10th Anniversary of JCM Recent Diagnostic and Therapeutic Advance in Gastroenterology and Hepatopancreatobiliary Medicine - Suzuki, Hidekazu (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The year 2021 marks the 10th anniversary of Journal of Clinical Medicine, and as one of the major sections of JCM, we are launching a 10th anniversary Special Issue in the section "Gastroenterology & Hepatopancreatobiliary Medicine". We accepted papers for the Special Issue, titled "Recent diagnostic and therapeutic advance in Gastroenterology & Hepatopancreatobiliary Medicine". This medical field is a complex and wide-ranging field that deals with diseases in multiple organs such as the gastrointestinal tract and hepatobiliary pancreas. With recent advances in diagnostic imaging and interventional treatment, those in endoscopic diagnosis and treatment, those in functional test and those in genetic diagnosis and drug therapy, including the molecular-targeted therapy, many new medical findings have been accumulated. In this Special Issue, we looked for reports that make full use of advances in diagnostics and therapeutics in the field of Gastroenterology and Hepatopancreatobiliary Medicine.